Radiographic Evaluation of Root Canal Treatment Performed by Undergraduate Students, Part I; Iatrogenic Errors - da Silva, PatrÃcia Zambon; Ribeiro, Francisco Carlos; Xavier, Juliana Machado Barroso; Pratte-Santos, Rodrigo; Demuner, Cristina (Iranian Endodontic Journal, 2019)
Introduction: The root canal preparation is an important stage in the undergraduate teaching and must be handled with care. Iatrogenic mishaps may occur during this procedure which might compromise the success of endodontic treatment. The aim of this study was to determine, the frequency of iatrogenic errors in endodontic treatments provided by undergraduate dental students at the School of Dentistry of Federal University of Espírito Santo (UFES), Brazil. Methods and Materials: Radiographic records of 511 anterior teeth and pre-molars with endodontic treatment performed by undergraduate students, between 2012 and 2014 were randomly chosen. The final sample consisted of radiographic records of 397 teeth endodontically treated and were evaluated by using the projection of radiographic images. Iatrogenic errors that were detected in root filled teeth included: apical perforation, root perforation, furcation perforation, strip perforation, presence of fractured instruments, ledge and zip. Then they were classified, according to the absence or presence of iatrogenic errors, as adequate or inadequate. Results: According to the results, 7.3% of the teeth were inadequate, and there was no statistically significant difference among the groups of anterior teeth, incisors, or canines (P>0.05). A ledge was present in 6.54% of root canals, a zip in 0.75% of root canals, and only one root canal presented a fractured instrument. In teeth with moderate curvature, the root curvature was a factor that possibly influenced the occurrence of the ledge (P<0.05). Conclusion: The majority of root canal preparations showed a low occurrence of iatrogenic errors. Keywords: Dental Student; Endodontics; Errors; Iatrogenic; Radiography; Root Canal Therapy